From revolutionary texts to rebellious readers: What is Leitura Popular da Bíblia and is it really 'popular'?. (20th July 2020) - McGeoch, Graham
Abstract : Inspired by Paulo's Freire's popular education for adults and liberation theology's 'option for the poor', Leitura Popular da Bíblia (LPB) was pioneered among poor urban and rural communities throughout Latin America. It emphasised participatory methodologies, critical thinking and community solutions to problems interpreted as political. Importantly, in its early phase, it accompanied and was inserted into revolutionary political and social movements. This article addresses the methodology of LPB and asks critical questions about the notion of 'popular' deployed by some liberation theologies. It problematises the community-based presentation of popular in LPB and asks how LPB can transgress its traditional spaces – favelas, factories, student unions – into newly politicised territories that root emancipatory practices in gender, race and (inter-)religious experiences. The article draws on insights from the experiences of LPB currently used in popular movements in Brazil and Latin America, and considers the wider implications for LPB in light of changing popular experiences and changing practices in revolutionary political and social movements.